Jesus Christ, the Man for Others : The Suffering God in the thought of Paul Tillich and Dietrich Bonhoeffer - Reimer, A. (Laval théologique et philosophique)

(untitled) (Faculté de philosophie, Université Laval, 2006)
AbstractIn this essay I compare Bonhoeffer’s and Tillich’s perspectives on divine suffering and suggest that Bonhoeffer’s (and to a lesser degree Tillich’s) notion of both divine and human vicarious suffering is a way of re-framing Anselm’s so-called “forensic” theory of atonement, in which Christ takes upon himself the undeserved condemnation of fallen humankind and dies vicariously on our behalf in order to satisfy divine justice.